Communicatively Managing Multiple, Intersecting Identities Among Immigrant Women Entrepreneurs. (April 2021) - Haseki, Müge; Scott, Craig R.; Gailliard, Bernadette M.
Immigrant women comprise one of the fastest growing groups of business owners in the United States and other urban economies; however, a greater proportion of immigrant women business owners shut down their business within a year compared with their nonimmigrant peers. In an attempt to address this challenge, the study reported here explores the communication strategies adopted by immigrant women entrepreneurs as they manage key identities (gender, ethnicity, religion, and immigrant status) that may influence their success. Drawing on a structurational model of multiple identities and linking that with intersectionality research, this study examines the experiences of 60 immigrant women entrepreneurs from 30 different countries in New York City as they (dis)connect with their various identities. In addition to insights about each separate identity, we identify three tensions at the intersection of multiple identities, business sector, and sociocultural and historical context: visible versus invisible, expressive versus silent, and revealing versus concealing . Furthermore, we show how strategic communication practices are adopted to negotiate these tensions, and hence secure and/or increase business opportunities and business survival.